Education for sustainability and physical education: a systematic scoping review - Royet, Thomas; Vors, Olivier; Cece, Valérian; Lentillon Kaestner, Vanessa (Sport, Education and Society)
Education for sustainability (EfS) in the school context is recognized scientifically and politically as fundamental for training citizens who are capable of transforming future society. Physical education (PE) represents a singular way to complement cognitive approaches by drawing on the bodily dimension and learning in action as well as affective and sensory aspects. Furthermore, relevant research could lead to the qualitative implementation of EfS in PE. Thus, the aim of this systematic scoping review was to summarize the results of related research into the implementation of EfS in PE and to identify avenues for future studies aimed at establishing EfS sequences within PE. A 5-step methodological framework, incorporating the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, was used to carry out this scoping review, in which 30 studies were considered. The results showed that the research was current, was performed mainly in Europe, and frequently referred to the institutional framework of the Sustainable Development Goals. Additionally, the results highlighted that PE programs make few explicit references to the concept of sustainability or EfS; furthermore, PE teachers, while they may be inclined to implement EfS in PE, lack control of the concepts and training. Finally, the EfS learning sequences in PE have limitations regarding the definition and characteristics of effective EfS, particularly a lack of pluralism and holism. Recommendations for future research and for practical implementation were made, particularly with respect to PE teacher training, PE programs and EfS learning sequences in PE.
Keywords: Education for sustainability; physical education; scoping review; sustainability; sustainable development